2000
DOI: 10.1161/01.cir.101.25.2902
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of the Na + /H + Exchange Inhibitor Cariporide in Patients With Acute Anterior Myocardial Infarction Undergoing Direct PTCA

Abstract: Our findings suggest that inhibition of Na(+)/H(+) exchange by cariporide may attenuate reperfusion injury and thereby improve the recovery from left ventricular dysfunction after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(132 citation statements)
references
References 32 publications
5
122
0
5
Order By: Relevance
“…Our results are in accordance with studies that reported the improvement of survival of different HF models following treatments with NHE-1 inhibitors (Kusumoto et al 2001;Engelhardt et al 2002;Chahine et al 2005;Baartscheer et al 2005). The experimental evidence implicating NHE-1 as a possible therapeutic target for the treatment of HF and its associated early death has sparked several clinical trials to test the efficacy of NHE-1 inhibitors in HF patients (Rupprecht et al 2000;Theroux et al 2000;Zeymer et al 2001). In one of these trials, the GUARDIAN study, a short-term treatment with cariporide reduced mortality of early post-infarction patients (Theroux et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in accordance with studies that reported the improvement of survival of different HF models following treatments with NHE-1 inhibitors (Kusumoto et al 2001;Engelhardt et al 2002;Chahine et al 2005;Baartscheer et al 2005). The experimental evidence implicating NHE-1 as a possible therapeutic target for the treatment of HF and its associated early death has sparked several clinical trials to test the efficacy of NHE-1 inhibitors in HF patients (Rupprecht et al 2000;Theroux et al 2000;Zeymer et al 2001). In one of these trials, the GUARDIAN study, a short-term treatment with cariporide reduced mortality of early post-infarction patients (Theroux et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…17,18 Sarcolemmal NHE-1 is expressed in human myocardium, 25 and clinical trials have demonstrated myocardial benefits derived from NHE-1 inhibition in subsets of patients undergoing emergent coronary revascularization. 26 Thus, effects similar to those reported here in pigs may also apply to humans and facilitate closed-chest resuscitation from VF. Clinical studies on NHE-1 inhibition during cardiac resuscitation are eagerly awaited.…”
Section: Discussionsupporting
confidence: 70%
“…6) These results suggest that NHE1 is activated in the ischemic and remodeling myocardium, and may play a key role in the development of heart failure after AMI. However, little is known about changes in NHE1 expression in the non-infarcted region after AMI.…”
Section: )mentioning
confidence: 75%